2022
DOI: 10.3390/app12031309
|View full text |Cite
|
Sign up to set email alerts
|

Remote and Proximal Sensing Techniques for Site-Specific Irrigation Management in the Olive Orchard

Abstract: The aim of this study was to evaluate the potential use of remote and proximal sensing techniques to identify homogeneous zones in a high density irrigated olive (Olea europaea L.) orchard subjected to three irrigation regimes (full irrigation, deficit irrigation and rainfed conditions). An unmanned aerial vehicle equipped with a multispectral camera was used to measure the canopy NDVI and two different proximal soil sensors to map soil spatial variability at high resolution. We identified two clusters of tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In the second case, ToW, cultivar PT obtained a negative trend. On the other hand, SC showed a positive trend, confirming the results of previous studies [ 48 , 49 ]. The results show that the effect of cultivar must be considered in the use and study of VIs in olive grove management.…”
Section: Discussionsupporting
confidence: 91%
“…In the second case, ToW, cultivar PT obtained a negative trend. On the other hand, SC showed a positive trend, confirming the results of previous studies [ 48 , 49 ]. The results show that the effect of cultivar must be considered in the use and study of VIs in olive grove management.…”
Section: Discussionsupporting
confidence: 91%
“…In regard to the use of UAV platforms, Jorge et al [152] used an MSP sensor to detect irrigation variations, finding strong correlations between NDVI and Green Normalized Difference Vegetation Index (GNDVI) [236]. Caruso et al [143] assessed irrigation effects using both RGB and MSP sensors, highlighting significant water savings with minimal yield impact under deficit irrigation (DI). Santos-Rufo et al [168] compared subsurface drip irrigation and surface drip irrigation impacts using RGB and HSP sensors coupled to UAVs.…”
Section: Irrigation Management and Water Stress Indicator Estimationmentioning
confidence: 99%
“…The authors showed that the NDVI and photochemical reflectance index (PRI; a further VI calculated in the VIS region) were the indices that best correlated with the Ψ stem (R 2 = 0.61 and 0.65, respectively), whereas, for analyzing within single species, peach and 'Garrigue' almond were found to be the most suitable species for the prediction of both the Ψ stem and g s from NDVI data (R 2 = 0.72 and 0.74 for Ψ stem and R 2 = 0.75 and 0.71 for g s , respectively). In olive, Caruso et al [265] demonstrated that the NDVI can be a reliable indicator of tree water stress. In grapevine, several works confirm that the NDVI can be a good indicator of PWS [266][267][268][269].…”
Section: Multispectral Sensingmentioning
confidence: 99%
“…To date, there is not a large number of studies combining remote and proximal sensing. Caruso et al evaluated the combined use of multispectral data from UAVs with data from soil electrical conductivity sensors in order to identify homogeneous zone in a high-density irrigated olive orchard [265]. The authors found that the impact of various irrigation strategies on tree performance and water use efficiency (WUE) is location-dependent within the orchard, and tree vigor emerges as a primary factor influencing the ultimate fruit yield when the soil water availability is optimal.…”
Section: Combined Approaches Of Proximal and Remote Sensingmentioning
confidence: 99%